2016
DOI: 10.1039/c6sm00812g
|View full text |Cite
|
Sign up to set email alerts
|

Correlation lengths in hydrodynamic models of active nematics

Abstract: We examine the scaling with activity of the emergent length scales that control the nonequilibrium dynamics of an active nematic liquid crystal, using two popular hydrodynamic models that have been employed in previous studies. In both models we find that the chaotic spatio-temporal dynamics in the regime of fully developed active turbulence is controlled by a single active scale determined by the balance of active and elastic stresses, regardless of whether the active stress is extensile or contractile in nat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
90
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 39 publications
14
90
1
Order By: Relevance
“…or velocity are all controlled mainly by the mean defect spacing ξ ∼ 1/ √ n, in agreement with previous numerical results [26,27].…”
Section: B Results and Outlinesupporting
confidence: 92%
“…or velocity are all controlled mainly by the mean defect spacing ξ ∼ 1/ √ n, in agreement with previous numerical results [26,27].…”
Section: B Results and Outlinesupporting
confidence: 92%
“…2a). This parameter characterizes the ratio of the channel height h , which here is equivalent to the hydrodynamic screening length, to the characteristic activity-induced length scale , which represents the relative importance of the intrinsic activity ζ and the orientational elasticity K of the nematic fluid3334.…”
Section: Resultsmentioning
confidence: 99%
“…By varying these factors it is possible to observe diverse spatiotemporal patterns including vortices [14,16], oscillating textures [8,18] and travelling bands [8,16]. When the driving force is sufficiently high, active nematics can spontaneously nucleate many topological defects, generating flows and interacting chaotically in a regime referred to as low reynolds number, active turbulence [1,4,10,11]. These defects have been shown to exert an elastic torque on each other [19] and experiments have indicated that long range nematic order of defects is possible in a state of active turbulence [20] though this hasn't been reproduced theoretically.…”
mentioning
confidence: 99%